1996
DOI: 10.1016/0014-5793(96)00603-5
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylcarnitine, a surface‐active metabolite

Abstract: Palmitoylcarnitine is a well-known intermediate in mitochondrial fatty acid oxidation. Less known are its properties as a snrfactant, with a capacity to solubilize biological membranes similar to that of many synthetic detergents used in the biochemical laboratory. Some of the physico-chemical properties of palmitoylcarnitine may help to explain the need for coenzyme A-carnitine-coenzyme A acyl exchange during mitochondrial fatty acid import. The amphiphilic character of palmitoylcarnitine may also explain its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 43 publications
(49 reference statements)
1
31
0
Order By: Relevance
“…Furthermore, treatment of pregnant rats with carnitine resulted in a significant increase in total phospholipids and dipalmitoylphosphatidylcholine levels in fetal rat lungs (19,21). Palmitoylcarnitine is a form of carnitine that has been reported to have properties as a surface active molecule or surfactant, and functions as an intermediate in mitochondrial fatty acid oxidation (22). Palmitoylcarnitine may decrease the surface tension of the alveoli, and deficiency in palmitoylcarnitine may lead to the development of RDS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment of pregnant rats with carnitine resulted in a significant increase in total phospholipids and dipalmitoylphosphatidylcholine levels in fetal rat lungs (19,21). Palmitoylcarnitine is a form of carnitine that has been reported to have properties as a surface active molecule or surfactant, and functions as an intermediate in mitochondrial fatty acid oxidation (22). Palmitoylcarnitine may decrease the surface tension of the alveoli, and deficiency in palmitoylcarnitine may lead to the development of RDS.…”
Section: Discussionmentioning
confidence: 99%
“…The large amounts of acyl-CoA and acylcarnitine that accumulate in the mitochondrial matrix during ischemia accelerate mPTP opening and are directly released into the cytosol along with cytochrome c after mPTP opening (9,39,40). Prolonged Ca 2ϩ -induced opening of the mPTP that is facilitated by Ca 2ϩ activation of iPLA 2 ␥ causes irreversible dissipation of the mitochondrial membrane potential and loss of membrane integrity leading to extensive mitochondrial damage (41).…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain acyl-CoA esters were, in comparison with fatty acids and lysophospholipids, the most potent disrupter of membrane bilayers [4]. In contrast, it has been shown that only acylcarnitines, and not acyl-CoAs, are able to disrupt membrane barriers to solutes and produce complete membrane solubilization [6,7,9,10].…”
Section: Physical Properties Of Long-chain Acyl-coa Esters and Their mentioning
confidence: 99%